Characterization of the Theileria parva sporozoite proteome - Nyagwange, James (Int J Parasitol, 2018)
East Coast fever is a lymphoproliferative disease caused by the tick-borne protozoan parasite Theileria parva. The sporozoite stage of this parasite, harboured and released from the salivary glands of the tick Rhipicephalus appendiculatus during feeding, invades and establishes infection in bovine lymphocytes. Blocking this initial stage of invasion presents a promising vaccine strategy for control of East Coast fever and can in part be achieved by targeting the major sporozoite surface protein p67. To support research on the biology of T. parva and the identification of additional candidate vaccine antigens, we report on the sporozoite proteome as defined by LC–MS/MS analysis. In total, 4780 proteins were identified in an enriched preparation of sporozoites. Of these, 2007 were identified as T. parva proteins, representing close to 50% of the total predicted parasite proteome. The remaining 2773 proteins were derived from the tick vector. The identified sporozoite proteins include a set of known T. parva antigens targeted by antibodies and cytotoxic T cells from cattle that are immune to East Coast fever. We also identified proteins predicted to be orthologs of Plasmodium falciparum sporozoite surface molecules and invasion organelle proteins, and proteins that may contribute to the phenomenon of bovine lymphocyte transformation. Overall, these data establish a protein expression profile of T. parva sporozoites as an important starting point for further study of a parasitic species which has considerable agricultural impact.